Turkey and the European Union: Strategic Part- ners or Competitors in the Western Balkans? - Dursun-Özkanca, Oya (Journal of Regional Security, 2018)
Since the 1990s, Turkey and the European Union (EU) have each increasingly pursued active foreign policies in the Western Balkans, aimed at establishing peace, stability, and security in the region. Over the past few years, Turkey’s active foreign policy approach has been frequently labelled as “Neo-Ottomanism”. Against this backdrop of deteriorating relations between the EU and Turkey, Turkey has been attempting to use its soft power potential to consolidate its political, economic, and cultural influence in the Western Balkans. Thearticleexplores the factors contributing to and hindering Turkish influence in the region. It then analyzes factors behind Turkey’s renewed activism within the context of recent developments in EU-Turkey relations. Drawing onan extensive series ofelite interviews conducted in Turkey, the United Kingdom, Serbia, and Bosnia from 2011 to 2013, the article concludes with an examination of whether Turkey and the EU may best be regarded as strategic partners or competitors in the region.